1997
DOI: 10.1103/physrevb.56.6376
|View full text |Cite
|
Sign up to set email alerts
|

Solution of a supersymmetric model of correlated electrons

Abstract: We consider the exact solution of a model of correlated electrons based on the superalgebra Osp(2|2). The corresponding Bethe ansatz equations have an interesting form.We derive an expression for the ground state energy at half filling. We also present the eigenvalue of the transfer matrix commuting with the Hamiltonian.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…Here, some preliminary results have indicated a very rich structure: it was indeed shown in [8] that the continuum limit of a particular osp(2/2) q model [9] coincided with the continuum limit of the well known Bukhvostov Lipatov model [10], providing the first example of an integrable "double sine-Gordon" model [11], [12]. The case of sl(N/K) q models based on fundamental representations has also been studied in some details [13], enough to show that they have a relativistic limit, but far from providing a complete identification of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Here, some preliminary results have indicated a very rich structure: it was indeed shown in [8] that the continuum limit of a particular osp(2/2) q model [9] coincided with the continuum limit of the well known Bukhvostov Lipatov model [10], providing the first example of an integrable "double sine-Gordon" model [11], [12]. The case of sl(N/K) q models based on fundamental representations has also been studied in some details [13], enough to show that they have a relativistic limit, but far from providing a complete identification of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the Hamiltonian in Ref. [26] differs from the bulk part (24), but that they are related to each other by a canonical transformation. Nevertheless, it will be shown that this transformation does not change the Bethe-ansatz equations in the bulk.…”
Section: The Solutions Of the Graded Rementioning
confidence: 99%
“…Models corresponding to non-exceptional Lie superalgebras as, for instance, gl(2|1) and osp(2|2) [24][25][26], have provided interesting non-perturbative information [27,28] for generalizations of well-known models such as, e.g., the Hubbard model [29]. A further generalization was achieved by considering the solution of the YBE related to the quantum superalgebra U q [osp(2|2)] [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their quantized versions can be shown to be affinizable to provide irreducible representations of the twisted quantum affine superalgebra U q ͓gl(m͉n) (2) ͔ from which trigonometric R matrices with U q ͓osp(m͉n)͔ invariance may be constructed. 4 These R matrices determine new integrable models that have generated remarkable interest in physics recently, [5][6][7] particularly in condensed matter physics, where they give rise to new integrable models of strongly correlated electrons.…”
Section: Introductionmentioning
confidence: 99%